Line Stop Time Reduction through Dandori Evaluation in Plastic Injection Process Production - Yohanes T. Wibowo; Anggi Pratama; Vuko A. T. Manurung (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2024)
A quality product is a product that is efficiently produced. Line stops should be minimized to ensure efficient production. This study found a high line stop in the area of plastic injection machines caused by dandori. The line stops account for about 6% of the total production time 5.3% of them caused by dandori. Dandori is a line stop due to tools changing within a production process. This study aims to reduce the line stop by 30% and uses a fishbone analysis enhanced by the 5W+1H method for further analysis to reduce this problem. Enhancing the fishbone diagram with 5W+1H analysis produces a positive result. As a written calculation, this improvement gives a 28% line stop reduction, but it provides an average of 32.5% in actual operation. The improvement succeeded in reducing line stops due to dandori. The final achievement of 32% has passed the target of a 30% reduction and also provides an excellent cost-benefit ratio value of 20.9.